(untitled) (Czech Journal of International Relations, 2002)
Boris Aronovič Chejfec: Kreditnaja historija Rossiji /Ot Jekatěriny II. do Putina/. 1. izdanie. Moskva: URSS, 2001, 133 s., ISBN 5-8360-0193-6; Boris Aronovič Chejfec: Vněšnyje dolgovyje aktivy Rossiji. 1. izdanie. Moskva: URSS, 2001, 206 s., ISBN 5-8360-0222-3.